Antibacterial Activity of Self-Nanoemulsifying Drug Delivery System (SNEDDSS) Loaded with Mangosteen (Garcinia mangostana L.,) Peels against Baccilus subtitis, Bacillus cereus, and Staphylococcus aureus isolated from Diabetic Foot Ulcer Patients - Liza Pratiwi (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Diabetic Foot Ulcer is a complication of diabetes mellitus characterized by open sores on the surface of the skin or mucous membranes as well as extensive dead tissue followed by bacterial invasion. Patients with Diabetic Foot Ulcer are resistant to some antibiotics so that alternative therapies such as potential traditional medicines involving mangosteen peels are being developed. Mangosteen peels contain compounds of phenolic, tannin, flavonoid, and xanton. To improve the stability of α-mangostin and improve bioavailability, it requires the preparation of Self-Nanoemulsifying Drug Delivery Systems (SNEDDS). This study aimed to analyze the antibacterial effect of optimal SNEDDS of ethyl acetate fraction from mangosteen peels against Bacillus subtilis, Bacillus cereus, and Staphylococcus aureus and to analyze the comparison of inhibition zone diameter between the optimal SNEDDS formula of the ethyl acetate fraction from mangosteen peels and ethyl acetate fraction without SNEDDS against the bacteria. This study began with making 70% ethanol extract from mangosteen peels which was then fractionated to obtain the ethyl acetate fraction. Furthermore, the ethyl acetate fraction was made into optimal SNEDDS formula resulted of Design Expert software with Tween 80, PEG 400, and VCO. The optimal SNEDDS formula of the ethyl acetate fraction from the mangosteen peels was tested for its antibacterial effectiveness against Bacillus subtilis, Bacillus cereus, and Staphylococcus aureus. The results revealed that SNEDDS loaded of ethyl acetate fraction from mangosteen peels had antibacterial activity against both types of Gram-positive bacteria, Bacillus subtilis, and Staphylococcus aureus, which cause diabetes ulcers, and that it did not have antibacterial activity against Bacillus cereus. Moreover, the tested SNEDDS loaded ethyl acetate fraction and ethyl acetate fraction without SNEDDS had strong inhibitory activity against Bacillus subtilis. Meanwhile, they provided such a smaller inhibition zone as tested against Staphylococcus aureus that they had moderate antibacterial activity.